Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
[tex] \sqrt{6x-9} = x[/tex]
first we are going to get rid of the square root by raising both sides to the power of 2
6x - 9 = x²
x² - 6x + 9 = 0
now the equation is a quadratic, and you can solve for x
i'm going to factor it, but there are many ways to solve for a quadratic
(x - 3)(x - 3) = 0
If you FOIL this, it becomes x² - 6x + 9
(x - 3)² = 0
x - 3 = 0
x = 3
to check the answer, you can plug 3 back into the original equation
[tex] \sqrt{6(3) - 9} = 3 [/tex]
[tex] \sqrt{18 - 9} = 3[/tex]
[tex] \sqrt{9} = 3[/tex]
[tex]3 = 3[/tex]
first we are going to get rid of the square root by raising both sides to the power of 2
6x - 9 = x²
x² - 6x + 9 = 0
now the equation is a quadratic, and you can solve for x
i'm going to factor it, but there are many ways to solve for a quadratic
(x - 3)(x - 3) = 0
If you FOIL this, it becomes x² - 6x + 9
(x - 3)² = 0
x - 3 = 0
x = 3
to check the answer, you can plug 3 back into the original equation
[tex] \sqrt{6(3) - 9} = 3 [/tex]
[tex] \sqrt{18 - 9} = 3[/tex]
[tex] \sqrt{9} = 3[/tex]
[tex]3 = 3[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.